Conductivity Effect on the Capacitance Measurement of a Parallel-Plate Capacitive Sensor System - Peyman Azimi Anaraki (Indonesian Journal of Physics, 2011)
In this article design and operation of a parallel-plate capacitive sensor based on the dielectric capacitance and conductance change of the gap medium is reported. The designed system was used to determine characteristics of different water liquids as a result of the capacitance variations. The air gap capacitance is measured and then by filling the gap with a liquid the capacitance is monitored for different liquids. Proposed sensor is used for the distilled, tap, boiled, and salt water measurements and the capacitance results are compared. A big difference about 45.5µF in capacitance values for the salt and distilled water shows a high sensitivity, which can be used to recognize different water liquids. The experimental results are promising for water liquids and verify the successful operation of such a device as a liquid sensor, a useful method for checking the electrical quality of the water that is required for different applications.